2021
DOI: 10.3390/ijms22126502
|View full text |Cite
|
Sign up to set email alerts
|

MUC16 Is Overexpressed in Idiopathic Pulmonary Fibrosis and Induces Fibrotic Responses Mediated by Transforming Growth Factor-β1 Canonical Pathway

Abstract: Several transmembrane mucins have demonstrated that they contribute intracellularly to induce fibrotic processes. The extracellular domain of MUC16 is considered as a biomarker for disease progression and death in IPF patients. However, there is no evidence regarding the signalling capabilities of MUC16 that contribute to IPF development. Here, we demonstrate that MUC16 was overexpressed in the lung tissue of IPF patients (n = 20) compared with healthy subjects (n = 17) and localised in fibroblasts and hyperpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Current evidence supports that CA125 plays an active role in promoting epithelial to mesenchymal transition, a biological process allowing polarized, immobile epithelial cells to undergo biochemical changes that enable them to assume a mesenchymal cell phenotype [ 1 , 11 ]. This change results in increased migratory capacity, invasiveness, elevated resistance to apoptosis, and greatly enhanced production of extracellular matrix components [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence supports that CA125 plays an active role in promoting epithelial to mesenchymal transition, a biological process allowing polarized, immobile epithelial cells to undergo biochemical changes that enable them to assume a mesenchymal cell phenotype [ 1 , 11 ]. This change results in increased migratory capacity, invasiveness, elevated resistance to apoptosis, and greatly enhanced production of extracellular matrix components [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…These epicardial-released adipokines have been associated with fibroblast proliferation, collagen synthesis, and myofibroblast activation [ 10 ]. Given that MUC16 can potentially be expressed in all mesothelial cells (including epicardium) and it is known to participate in modulating key fibrotic cellular processes such as epithelial-mesenchymal transition (EMT), fibroblast to myofibroblast transition, and fibroblast proliferation [ 1 , 11 ], we speculate that epicardial MUC16 could be associated with inflammatory and fibrotic processes in the human heart.…”
Section: Introductionmentioning
confidence: 99%
“…These apparent discrepant results might be explained, in part, by differences in disease etiologies, patient demographics, and/or lung sampling techniques between the various studies ( 201 , 203 , 204 ). The expression levels of MUC4 and MUC16 were elevated in patients with IPF, with evidence for each MUC4 and MUC16 promoting the fibrotic process in collaboration with TGF-β ( 206 209 ). Of particular prominence is a strong association of a gain-of-function MUC5B gene promoter variant (rs35705950) with pulmonary fibrosis ( 210 215 ).…”
Section: Neus and Mucs In Pulmonary Fibrosismentioning
confidence: 99%
“…Studies of human ovarian cancer have revealed that the cancer antigen CA125 can serve as a ligand of MSLN [ 76 , 77 ], and co-expression of MUC16 and MSLN is known to be associated with the invasion process of cancers [ 78 , 79 , 80 , 81 ], with MUC16 promoting the potential role of MSLN in tumor adhesion, and metastasis [ 76 , 82 ]. CA125 is widely accepted as a diagnostic marker of ovarian cancer and a number of other malignant conditions such as breast cancer, mesothelioma, non-Hodgkin lymphoma, pancreatic cancer, gastric cancer, and leiomyoma [ 83 ], with exemption of benign conditions including endometriosis, pregnancy, congestive heart failure, nephrotic syndrome, and fibrosis-associated disease including liver cirrhosis and pulmonary fibrosis [ 84 , 85 , 86 , 87 , 88 ]. Muc16 as well as Msln were identified as signature genes of aPFs isolated from mouse BDL liver [ 8 ], and Muc16 was shown to bind to Msln as the ligand, facilitating the TGFβ receptor-mediated activation cascade of PFs in cholestatic injury [ 14 ].…”
Section: Biological Function Of Mesothelin Muc16 and Thy1mentioning
confidence: 99%